Abrikossoff's Tumour Mimicking a Neoplastic Tumour of the Breast: A Case Report - Alassiri A; Al Ali A; Vaysse C; Escourrou G; Vinet B; Rimailho J (Global Journal of Cancer Therapy - Peertechz Publications, 2017)
Introduction: Granular cell tumours (GCT), also known as Abrikossoff's tumours, are rare, and occur in the breast in approximately 5-6% of the cases these tumours are usually benign with only 1% of malignancy. Case Presentation: A 57-year-old Caucasian woman presented with a palpable mass that was growing progressively in the axillary tail of the left breast, with no other associated symptoms, and no family history of breast cancer.  Discussion: It is important that this type of lesion be identifi ed clinically, radiologically and pathologically by all physicians managing breast tumours, in order to offer the most appropriate treatment. Using this classical clinical case, we will discuss the histological characteristics and the management of this type of lesion.  Conclusion: A biopsy of the lesion provided a defi nitive diagnosis, and a wide local incision was recommended as the treatment plan.